In Situ Reduced Graphene Oxide and Polyvinyl Alcohol Nanocomposites With Enhanced Multiple Properties - Hu, Wenwen; Liu, Shuhan; Wang, Zhonghai; Feng, Xianjing; Gao, Ming; Song, Fangming (Frontiers in Chemistry, 2022)
The nanocomposites formed by graphene oxide (GO) and carbazate modified polyvinyl alcohol (PVA-N) were developed to investigate their multiple properties for wide applications. Their physicochemical characterizations confirmed that the in situ reduced GO (rGO) not only decreased the crystallization but also induced the porous structures inside nanocomposites. Significantly, it revealed that the comprehensive performance of PVA-N2-2%GO consisted of PVA-N2 with the carbazate degree of substitution (DS) of 7% and weight ratio (wt%) of 2% GO displayed 79% of tensile elongation and tensile strength of 5.96 N/ mm2 (MPa) by tensile testing, glass transition temperature (Tg) of 60.8 ℃ and decomposition temperature (Td) of 303.5 ℃ by TGA and DSC, surface contact angle at 89.4± 2.1°, and electric conductivity of 9.95×10-11 S/ cm. The above comprehensive performance was enhanced with the increased amount of in situ rGO, contributed by the high DS of carbazate group in PVA-N and high amount of GO. The rGO by in situ reduction was the main driving force for enhancing the multiple properties inside nanocomposites.